Implementation of lean thinking principals to logistic activities: a case study in a wood forest industry - Fallas-Valverde, Paula (2018)
Integration between different parties in value-streaming mapping (VSM) can be a difficult task when internal and external operations at a company are not synchronized. An innovative lean-logistics performance system tool, based upon VMS’ strengths, was developed to aid in fulfilling this gap. This tool focuses in providing a holistic view of logistic activities with the goal of increasing the efficency of operational processes in the value stream. A case study was conducted in a wooden prefabricated panelized industry. The case consisted in evaluating the logistic activities through the application of lean logistics tools. The application of lean tools helped to identify excessive waste of in the form of inventories throughout the supply chain. Specifically, an economic order quantity (EOQ) model was proposed that resulted in a cost reduction of $220,254 annually in the supply chain. Inventory maintenance cost was decreased in 42%.In conclusion, the implementation of lean tools applied to logistics procedures was effective to improve logistic operations. The lean tools could be implemented in other industry settings as well.